2011
DOI: 10.1371/journal.pone.0027840
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Alterations and Associated Aberrant DNA Methylation Patterns across Multiple Sample Types in Oral Squamous Cell Carcinoma

Abstract: BackgroundMicroRNA (miRNA) expression is broadly altered in cancer, but few studies have investigated miRNA deregulation in oral squamous cell carcinoma (OSCC). Epigenetic mechanisms are involved in the regulation of >30 miRNA genes in a range of tissues, and we aimed to investigate this further in OSCC.MethodsTaqMan® qRT-PCR arrays and individual assays were used to profile miRNA expression in a panel of 25 tumors with matched adjacent tissues from patients with OSCC, and 8 control paired oral stroma and epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 52 publications
6
106
1
4
Order By: Relevance
“…Several groups have reported that reduced expression of miR-375 could be a biomarker for HNSCC. 18,21,37 The expression levels of miR-375 were found to be lower in oral SCC patient oral rinse and saliva compared with those in healthy controls. 21 The expression ratio miR-221:miR-375 could be useful for distinguishing HNSCC from normal epithelium.…”
Section: Aberrant Expression and Functional Significance Of Mir-375 Imentioning
confidence: 97%
See 3 more Smart Citations
“…Several groups have reported that reduced expression of miR-375 could be a biomarker for HNSCC. 18,21,37 The expression levels of miR-375 were found to be lower in oral SCC patient oral rinse and saliva compared with those in healthy controls. 21 The expression ratio miR-221:miR-375 could be useful for distinguishing HNSCC from normal epithelium.…”
Section: Aberrant Expression and Functional Significance Of Mir-375 Imentioning
confidence: 97%
“…18,21,37 The expression levels of miR-375 were found to be lower in oral SCC patient oral rinse and saliva compared with those in healthy controls. 21 The expression ratio miR-221:miR-375 could be useful for distinguishing HNSCC from normal epithelium. 18 Another report showed that low miR-375 expression levels significantly correlated with cancer survival and distant metastasis.…”
Section: Aberrant Expression and Functional Significance Of Mir-375 Imentioning
confidence: 97%
See 2 more Smart Citations
“…MiR-375 was confirmed as a strongly repressed miRNA in OSCC. Wiklund et al reported a 10-fold decrease of expression in tumours compared to matched adjacent tissue, and a 1000-fold change when compared to healthy epithelium [70]. They also suggested that miRNA-375 was probably epithelial specific, highlighted by two orders of magnitude higher miR-375 expression in healthy epithelium than stroma.…”
Section: Mirna Profile Of Oral Squamous Cell Carcinomamentioning
confidence: 99%